2020
DOI: 10.1109/access.2020.3013561
|View full text |Cite
|
Sign up to set email alerts
|

Combination of IMM Algorithm and ASTRWCKF for Maneuvering Target Tracking

Abstract: In this paper, an improved interactive multiple model adaptive strong tracking random weighted cubature Kalman filter (IIMM-ASTRWCKF) algorithm is developed to overcome the low tracking accuracy and easy divergence when dealing with complex maneuvering situations. The algorithm is improved in two aspects: On the one hand, ASTRWCKF is used as the sub filter of IMM algorithm to filter different motion models. By introducing the random weight factor to replace the original weight factor, the accuracy of the algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To validate the effectiveness of the proposed method, this section conducts simulations on the following seven robust state estimators: (1) the proposed multiple adaptive factors based interacting multiple model estimator (MAFIMME), (2) the original robust state estimator (RE), (3) the robust estimators with MR adaptive factor (MRRE), ( 4) the robust estimators with Huber adaptive factor (HRE), ( 5) the robust estimators with RMA adaptive factor (RMARE), ( 6) the robust estimators with Mahalanobis adaptive factor (MRE) and ( 7) the adaptive strong tracking cubature Kalman filter (ASTCKF) [22]. The simulation details and parameter descriptions are provided as follows:…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the effectiveness of the proposed method, this section conducts simulations on the following seven robust state estimators: (1) the proposed multiple adaptive factors based interacting multiple model estimator (MAFIMME), (2) the original robust state estimator (RE), (3) the robust estimators with MR adaptive factor (MRRE), ( 4) the robust estimators with Huber adaptive factor (HRE), ( 5) the robust estimators with RMA adaptive factor (RMARE), ( 6) the robust estimators with Mahalanobis adaptive factor (MRE) and ( 7) the adaptive strong tracking cubature Kalman filter (ASTCKF) [22]. The simulation details and parameter descriptions are provided as follows:…”
Section: Simulationmentioning
confidence: 99%
“…One primary method to address the unpredictable increase in observation noise involves introducing adaptive factors. This entails assessing and adjusting the estimation error covariance, process noise covariance, and observation noise covariance based on residuals to enhance estimation accuracy [21][22][23]. The adaptive strong tracking cubature Kalman filter (ASTCKF) method proposed in [22] accomplishes corrections to all three, thereby enhancing estimator performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To implement higher tracking accuracy for the maneuvering target tracking, many improved strong tracking cubature Kalman filter (STCKF), such as strong tracking spherical simplex-radial CKF [ 28 ], fifth-degree STCKF [ 29 ], Bayesian-based strong tracking interpolatory CKF [ 30 ], model-based strong tracking square-root CKF [ 31 ], have recently been proposed. In addition, Ma et al [ 32 ] added STF into the sub-filter of IMM to overcome the low tracking accuracy when dealing with maneuvering situations. However, in practical applications, it is found that the detection and tracking ability of the STF method will be reduced when the maneuver of the target is small.…”
Section: Introductionmentioning
confidence: 99%